Thai Senior tourists: Explore of Travel Constraints, Recreational Activities and Travel Intention - Prasongthan, Supaporn; Thanandornsuk, Karinthorn; Charoenbunprasert, Sannit (Rajamangala University of Technology Tawan-ok Social Science Journal, 2021)
The purpose of this study is three-fold: (1) to explore travel constraints which correlate to travel intention (2) to investigate recreation activities which seniors interested during traveling which correlate to travel intention and (3) to study the current situation regarding the tourism promotion for Thai seniors of the relevant authorities both government sector and private sector. Mixed methods research design were used in this study. The quantitative data were collected from 396 samples and qualitative data were analyzed from interviewed date with five key informants who involved in senior tourism. The results showed that Thai senior tourists had high travel intention and interested in recreation activities during traveling. The demands of this group are different from other age groups for example package tour, facilities etc. due to span of age and health-related problem which are travel constraints. Therefore, this study recommends that for promoting the tourism for Thai seniors. The stakeholder should give important to this group for government should follow the policy that concerned about senior tourism and collaborate with travel agency for support the tourism for Thai senior .Travel agency also should develop the company policy for support this group.